To determine which table shows that \( y = -f(x) \) results in a reflection over the x-axis, we need to look for a table of values where the \( -f(x) \) values are the negative of the corresponding \( f(x) \) values.
Let's evaluate the provided tables:
-
x -f(x) -2 0 -3 1 -6 2 x f(x) -2 0 -3 1 -6 2
Here, \( -f(-2) = -0 = 0 \), \( -f(-3) = -1 \), \( -f(-6) = -2 \). This does not reflect the values.
-
x -f(x) -2 0 -3 -1 -6 -2 x f(x) -2 0 -3 1 -6 2
Here, \( -f(-2) = -0 = 0 \), \( -f(-3) = -1 \), \( -f(-6) = -2 \). This matches the functionality \( -f(x) = -f(x) \) for the corresponding \( f(x) \).
-
x -f(x) 2 0 3 -1 6 -2 x f(x) 2 0 3 -1 6 -2
This set gives \( -f(2) = -0 = 0 \), \( -f(3) = 1 \), \( -f(6) = 2 \). This does not reflect properly.
-
x -f(x) 2 0 3 1 6 2 x f(x) 2 0 3 1 6 2
Here, \( -f(2) = -0 = 0 \), \( -f(3) = -1 \), \( -f(6) = -2 \). This does not reflect properly.
Based on this evaluation, the second table is the only one that correctly shows that \( y = -f(x) \) results in a reflection over the x-axis.
Thus, the answer is the second table:
x -f(x)
-2 0
-3 -1
-6 -2
x f(x)
-2 0
-3 1
-6 2